Oblate Spheroidal Triboelectric Nanogenerator for All‐Weather Blue Energy Harvesting. Issue 26 (27th May 2019) - Liu, Guanlin; Guo, Hengyu; Xu, Sixing; Hu, Chenguo; Wang, Zhong Lin
Abstract: Triboelectric nanogenerators (TENGs) provide one of the most promising techniques for large‐scale blue energy harvesting. However, lack of reasonable designs has largely hindered TENG from harvesting energy from both rough and tranquil seas. In this paper, an oblate spheroidal TENG assembled by two novel TENG parts is elaborately designed for both situations. The TENG in the upper part is based on spring steel plates without other substrate materials, which makes it possible to output considerable power in rough seas and occupy small space. The TENG in the lower part consists of two copper‐coated polymer films and a rolling ball which can capture small wave energy from tranquil seas. The working mechanism and output performance are systematically studied. A maximum open‐circuit voltage of 281 V and a short‐circuit current of 76 µA can be achieved by one upper part, enough to charge a commercial capacitor for potential applications. More important, the proposed oblate spheroidal shell not only guarantees high sensitivity of the TENG in the lower part, but also qualifies the TENG with unique self‐stabilization and low consumables for the next generation of TENGs with new structural design toward all‐weather blue energy harvesting. Abstract : An oblate spheroidal triboelectric nanogenerator assembled by two novel triboelectric nanogenerator parts elaborately designed for different oceanic conditions, from rough seas to tranquil seas, demonstrates a new strategy for all‐weather blue energy harvesting. It also is proved to possess unique self‐stabilization, high sensitivity, and low consumables.